Pooling and sharing in the EU and NATO: European defence needs political commitment rather than technocratic solutions - Christian Mölling (Stiftung Wissenschaft und Politik (SWP), 2012)
At NATO Summit and EU Councils alike states praise pooling and sharing (P&S) as a kind of technocratic miracle cure for their impending inability to act militarily. That states will benefit economically from pooling their military capabilities sounds plausible. However, it remains unclear how the curtailment of sovereignty that such pooling necessarily involves should be accomplished. Consequently, the initiatives launched to date have not been particularly successful. Moreover, P&S does not replace either the investments needed to procure lacking military capabilities or the political framework that defines how such capabilities should be deployed. Rather than constantly looking out for new individual projects, states must resolve these tricky questions. At present, Europe is running the risk of talking to death another sensible option for maintaining its defence capability
Keywords: 320